The efficacy and toxicity of induction chemotherapy plus concurrent chemoradiotherapy in locoregionally advanced nasopharyngeal carcinoma: A meta-analysis of randomized controlled trials. Issue 10 (March 2020) - Wang, Peirong; Zhang, Mingwei; Ke, Chunlin; Cai, Chuanshu
Abstract: Background: A systemic review and meta-analysis of randomized controlled trials (RCTs) was performed to compare the efficacy, toxicity and safety of concurrent chemoradiotherapy (CCRT) with or without induction chemotherapy (IC) for locoregionally advanced nasopharyngeal carcinoma (NPC). Methods: Research searching was performed in Web of Science, PubMed, The Cochrane Library, Embase, Chinese Biomedical Database, Chinese National Knowledge Infrastructure, Chongqing VIP Database for Chinese Technical Periodicals and Wanfang Database. RCTs including patients diagnosed with locoregionally advanced NPC without metastasis and randomly treated with IC plus CCRT and CCRT alone were included. Survival and outcome data were extracted and meta-analysis was performed using the Revman 5.3.0 software. Results: Ten RCTs (2280 patients) were selected and used for pooled meta-analysis. In comparison with CCRT, IC plus CCRT treatment significantly improved the overall survival (OS; HR = 0.70, 95%CI 0.56–0.87, P = .002), progression-free survival (PFS; HR = 0.75, 95%CI 0.65–0.87, P < .0001), distant metastasis failure-free survival (DMFS; HR = 0.71, 95%CI 0.58–0.85, P = .0003) and loco-regional failure-free survival (LFES; HR = 0.72, 95%CI 0.59–0.88, P = .002) of patients with locoregionally advanced NPC. Patients treated with IC and CCRT had higher incidence of grade 3–4 leucopenia and thrombocytopenia than patients treated with CCRT alone ( P < .0001). No significant difference in other grade 3–4 adverse events and radiation toxicity was observed between the two groups. IC combined with CCRT improved the survival of patients with locoregionally advanced NPC. Conclusions: Combined IC and CCRT therapy was an efficacy treatment regimen for locoregionally advanced NPC. Abstract : Supplemental Digital Content is available in the text